Designing a filament recycling extruder - Kmetz, Barbara; Takács, Ágnes (Design of Machines and Structures, 2021)
In this paper we can read about designing and building a filament recycling machine especially designed for 3D printers. 3D printing is quite popular nowadays, but unfortunately the base material of this technique is polymer, which is not an environmentally friendly material, but it can be recycled in most of the cases. The filament pieces are shredded beforehand with a shredding machine to get the appropriate size. After being chopped up and heated up to the given temperature, according to the materials specific parameters the filament can be melted down and extruded again. The study deals with designing a recycling machine as mentioned.